The Artificial Intelligence Revolution in Accounting and Auditing: Opportunities, Challenges, and Future Research Directions - Luthfiani, Anin Dyah (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to provide an overview of the increasing role of artificial intelligence in accounting and auditing. This is supported by the expertise of the accounting and auditor profession which has evolved with advances in technology from the use of pencil and paper to calculators, and eventually spreadsheets and accounting software. This study uses a conceptual approach and semi-systematic review in analyzing published relevant articles. The main results of this study explain that interdisciplinary collaboration is a must with respect to research conducted in the field of AI in accounting and auditing. Wider application of AI in the accounting and auditing professions is expected to deliver greater efficiency, productivity and accuracy benefits while burdening with the challenges of income and wealth inequality, traditional job extinction and an unskilled workforce. Careful preparation is needed on the part of educators, regulators and professional bodies by overcoming paradigm shifts and preparing future students, policymakers and professionals to face the challenges of a world full of big data, blockchain technology, artificial intelligence to deliver success in facing the fourth industrial revolution.